Main metabolic differences between hemibiotrophic plant pathogens Phytophthora infestans and Phytophthora betacei during infection in different hosts (2020)
The genus Phytophthora includes species of pathogens with the ability to infect a wide range of hosts. The most studied species in the clade is Phytophthora infestans. This oomycete is the causal agent of the late blight, a potentially devastating plant disease of tomato (Solanum lycopersicum) and potato (Solanum tuberosum), infecting leaves, stems and fruits of the plant. The new late blight outbreak found in tree tomato, Solanum betaceum, warned researchers about a new species capable of infecting solanaceous crops. Molecular studies and several infection tests allowed Phytophthora betacei to be identified as a new species. This new report generated questions about the differences between both plant pathogens, in order to identify the main differences between them regarding the host preference and the duration of their life cycle inside the host. One possible explanation might reside on the metabolism. Metabolic dissimilarities could be linked to metabolic pathways related with the generation of pathogenicity and/or virulence factors in a particular host. In the present study, genome-scale metabolic models (GSMMs) were obtained to identify the unique and shared metabolism between these two species, P. infestans and P. betacei. A total of 930 shared reactions were identified between the two metabolic models. Purine, pyrimidine and fatty acid biosynthesis were found as most represented pathways in the amount of reactions related with the biosynthesis of pathogenicity precursors. Concerning the unique features of the metabolism, N-Glycan biosynthesis was the most represented in P. betacei compared to P. infestans, and flavonoid biosynthesis was the most represented in P. infestans compared to P. betacei. Finally, context-specific models (CSMs) were obtained to identify the main metabolic differences between both oomycetes in different days post inoculation.